Evaluating the Effects of Three High Intensity Interval Training Protocols on Maximum Oxygen Consumption and Leg Strength in Recreational Football Athletes - Sonchan, Wirat; Sonchan, Saralee; Longrak, Ratanyoo (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to examine the effects of three high intensity interval training (HIIT) protocols on VO₂max and leg strength in recreational football athletes. Materials and methods. Thirty-one participants were recruited and randomly assigned to one of three HIIT protocols: HIIT20/20, HIIT40/10, or HIIT60/5. The training programs spanned 6 weeks with a frequency of 3 sessions per week on non-consecutive days. Baseline testing for VO₂max and leg strength was conducted using an incremental exercise test with blood gas analysis and an isokinetic machine, respectively, at 1 week before the intervention, and post-intervention testing occurred 1 week after the last training session. A two-way repeated measures ANOVA was employed to compare changes between groups and across time points. Results. The results demonstrated that there was a significant increase in VO₂max in both the HIIT40/10 (∆10.4 %, CI95% = 1.67–7.42 ml/kg/min, ES = Moderate) and HIIT60/5 (∆12 %, CI95% = 2.28–8.84, ES = Moderate) groups, while no considerable changes were observed in leg strength across any group (p > 0.05). Additionally, a Weak but substantial correlation between leg strength and VO₂max was found at both pre-intervention (r = 0.39) and post-intervention (r = 0.38) periods. Conclusions. In conclusion, if the training goal was to improve VO₂max through HIIT, both the HIIT40/10 and HIIT60/5 protocols were more effective than HIIT20/20.